Filipino American psychology a handbook of theory, research, and clinical practice - Nadal, Kevin L. (John Wiley & Sons, 2011)
Addressing the mental health needs of the Filipino American population - an often invisible, misunderstood, and forgotten group - Filipino American Psychology provides counselors and other mental health practitioners with the knowledge, awareness, and skills they can use to become effective and culturally competent when working with their Filipino American clients.